Differifiation of economic activities in the Romanian rural area through European non-refundable funds - Andreea Daniela Giucǎ (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. International Symposium. 12th Edition, 2021)
The diversification of economic activities in rural areas is a topical issue and can be a fundamental strategy for the development of the Romanian rural area, because it can produce a beneficial effect from an economic point of view, by increasing the income of the rural population.The Romanian rural area is characterized by a weak economic diversification and a major dependence on agricultural activities, which leads to low incomes for farmers. The practice of agriculture represents the essential / primordial activity in the rural environment, because it has a diversity of natural resources, having a strong economic and social potential. Due to the variety of natural conditions at its disposal, agricultural occupations occupy a dominant share in all economic activities carried out in rural Romania. The rural workforce should be directed to other economic activities, especially in services, based on accurate and ongoing information, human resources awareness and training. National rural employment strategies include measures to improve the quality of human resources to facilitate access to employment in non-agricultural economic activities.This paper aims to highlight the importance of developing and diversifying economic activities in rural areas, thus promoting entrepreneurial initiatives and the implementation of integrated actions for the development of local products. This study analyzes the impact of projects carried out through measure 312 "Support for the creation and development of micro- enterprises" of the National Rural Development Program 2007 - 2013, on economic development in rural areas and assess whether investments for the establishment, development and the modernization of non-agricultural enterprises has contributed to this development as well as to the reduction of rural migration.
Keywords: R11; 330; rural; economy; rural development; non-agricultural activities; micro-enterprises